2015
DOI: 10.21890/ijres.23596
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning with Technology: Effectiveness of ICT Integration in Schools

Abstract: Integration of Information, Communication, and Technology (ICT) will assist teachers to the global requirement to replace traditional teaching methods with a technology-based teaching and learning tools and facilities. In Malaysia, ICT is considered as one of the main elements in transforming the country to the future development. The Ministry of Education, through the latest Education Blue print (2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022)(2023)(2024)(2025), insights the importance of technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
610
2
40

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 777 publications
(698 citation statements)
references
References 18 publications
46
610
2
40
Order By: Relevance
“…The frequency of using frogVLE while teaching science and the time allocated each time when using frogVLE was low when compared to the number of times for teaching science in a year [2]. This finding is supported by the previous studies conducted to determine the use of ICT in teaching [8,9,12,13,19,20,27,28]. Teachers only used some of the applications found in frogVLE when teaching science while there are more applications that can be explored and applied to create interactive and engaging learning.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The frequency of using frogVLE while teaching science and the time allocated each time when using frogVLE was low when compared to the number of times for teaching science in a year [2]. This finding is supported by the previous studies conducted to determine the use of ICT in teaching [8,9,12,13,19,20,27,28]. Teachers only used some of the applications found in frogVLE when teaching science while there are more applications that can be explored and applied to create interactive and engaging learning.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies indicated that frogVLE has a great effectiveness for both teachers and students [8,9]. FrogVLE has created great interest among students and easy access to a wealth of materials and resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, to create a golden generation of Indonesia, this is also needed to prepare students to have 21st-century competence, namely critical thinking and problem-solving skills, collaboration skills, creativity skills, and communication skills [9]. This can be supported by using technology-based learning media [10]. Learning media is one of the factors for learning success.…”
Section: Introductionmentioning
confidence: 99%
“…Technology integration in education has revealed many benefits to educators and students due to the fact that students are familiar with technology and they will learn better within technology-based environment [11]. Unfortunately, limitation of using technology must be considered.…”
Section: Introductionmentioning
confidence: 99%